2017
DOI: 10.20452/pamw.4145
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease affects the angiographic presentation and outcomes of patients with coronary artery disease treated with percutaneous coronary interventions

Abstract: INTRODUCTION    The incidence of chronic obstructive pulmonary disease (COPD) in patients treated with percutaneous coronary intervention (PCI) is underestimated, and the effect of COPD on atherosclerosis and the outcomes of PCI is not fully understood. OBJECTIVES    The aim of this study was to assess the impact of COPD on periprocedural outcomes of PCI, as well as its relationship with clinical presentation and the type of coronary artery lesions. PATIENTS AND METHODS    Data were prospectively collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…Probably because of the major concern regarding the use of spirometry in patients presenting with heart attack,8,34 spirometry was systemically applied to determine all participants with COPD in only one among related PCI studies 24. Our approach was used in previous studies,13,18,19,22,23,25 and has been considered robust enough to identify patients with real-world COPD 15. In addition, a fraction of data missing or miscoding is inherent in studies using a large database, eg, COPD exacerbation accompanied by cardiac events or cardiac events per se being potentially misclassified as COPD exacerbation because of their similar clinical presentation, but such errors are likely random from a nationwide database and should not be a valid argument for our findings as nondifferential misclassification may lead to a bias toward the null.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably because of the major concern regarding the use of spirometry in patients presenting with heart attack,8,34 spirometry was systemically applied to determine all participants with COPD in only one among related PCI studies 24. Our approach was used in previous studies,13,18,19,22,23,25 and has been considered robust enough to identify patients with real-world COPD 15. In addition, a fraction of data missing or miscoding is inherent in studies using a large database, eg, COPD exacerbation accompanied by cardiac events or cardiac events per se being potentially misclassified as COPD exacerbation because of their similar clinical presentation, but such errors are likely random from a nationwide database and should not be a valid argument for our findings as nondifferential misclassification may lead to a bias toward the null.…”
Section: Discussionmentioning
confidence: 99%
“…However, outcomes of patients experiencing recent hospitalized exacerbations before PCI have not been elucidated. Also, some studies demonstrated that COPD patients were at increased risk for hospital mortality,13,18,20 while others did not find an adverse effect of COPD 12,1417,19. In the era of widespread use of PCI, the prognostic significance of COPD and recent hospitalized exacerbations need further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Prospectively collected data on PCI practice in Poland were obtained from the ORPKI Polish National dataset, which is coordinated nationwide by Jagiellonian University Medical College in cooperation with AISN PTK (Association of Cardiovascular Interventions, Polish Cardiac Society). Database characteristics and data collection methods have been previously published [3, 57]. Patients were categorized according to whether they were treated with RA or not over a 4-year period (2014–2017).…”
Section: Methodsmentioning
confidence: 99%
“…Our study confirmed that STEMI patients had a high rate of no-reflows (2.8%), CAs (2.6%), and the overall periprocedural complication rate was also high (6.2%) compared to other clinical presentations of CAD. Moreover, the relationship between no-reflows and the COPD as a prothrombotic state have been more widely discussed in two previously published manuscripts [ 17 , 18 ]. Furthermore, according to our knowledge, this is the first study verifying that among several confirmed predictors, smoking and COPD are independent risk factors of a higher incidence of no-reflows in patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%